Uncovering the global host cell requirements for influenza virus replication via RNAi screening - Stertz, Silke (2011)
Influenza virus is reliant on numerous host cell functions during its replication cycle. RNA interference technology, applied on a genome-wide level, has identified human host factors that are necessary for efficient virus replication and provides new insight into how influenza virus interacts with its host at the molecular level.